PERILAKU LIMINAL MASYARAKAT SASAK-LOMBOK DALAM BÊKAYAQ BAU NYALÉ DAN PATAQ PARÉ - Saharudin Saharudin (Unit Penelitian dan Publikasi Fakultas Ilmu Budaya Universitas Gadjah Mada, 2016)
This paper studied the socio-psychological issues found in the cultural event bêkayaq bau nyalé and bêkayaq pataq paré among Sasak agrarian society in the southern of the Lombok Island. The study examined the language used in the two types of bêkayaqs (reverberate poem activities) used an ethnopoetic perspective. The socio-psychological problems of the people were revealed and explained by an ethnohermeneutic and process analysis perspectives. Data were collected by observation and interview techniques. The results showed that the tradition of bêkayaq bau nyalé and pataq paré were not only verbal-artistic expressions, but also had a deep implication for the disclosure of the socio-cultural pressures of the culprit during their life in which they had to obey the obligations of the social and cultural normative structures. Through bêkayaq, they could remove their burdens (though it was only temporal). The main purpose of bêkayaq was to create a liminal world between women and men, at least in public area communication. The changes in the orientation of bau nyale, the inclusion of structural context (power), and the rationalization of rice farming, had an impact on people's behavior changes to the actors of bêkayaq.